Caracterização química e atividade antimicrobiana do óleo essencial, extrato bruto e frações de Piper callosum Ruiz & Pav. (Piperaceae) - Queiroz, César Castelo Branco de (Brasil, 2021)
The Piper callosum species is one of the more than 3,700 species belonging to the Piperaceae family, being popularly known as “electric oil. Its leaves and stalks are used in the form of tea to treat dysentery, nausea, dysmenorrhea, rheumatic and muscle pain, and as a natural repellent. These effects can be attributed to substances present in its leaf extracts, belonging to the classes of amides, steroids and alkaloids. Therefore, the objective of this work was to evaluate the chemical composition of the essential oil, crude extract and fractions of Piper callosum and to evaluate the antimicrobial activity against the microorganisms Escherichia coli, Staphylococcus aureus, Candida albicans and Candida parapsilosis. The extract was fractionated by liquid-liquid partition with hexane, chloroform, ethyl acetate and butanol. Essential oils were obtained by hydrodistillation of fresh material in a Clevenger apparatus. The chemical profile of crude extract and fractions was analyzed through chromatic reactions in tubes and thin-layer chromatography. The determination of chemical constituents of essential oils was carried out through gas chromatography analysis coupled with mass spectrometry. The crude extract, fractions and essential oils were submitted to the antimicrobial activity test. The yields of the crude extract, hexane, chloroform, ethyl acetate, butanol and hydroalcoholic fraction were respectively 19.22%, 15.13%, 1.64%, 1.45%, 10.41% and 71.35%. Three fractions of essential oils were obtained, with yields of 0.36% in OE1 (densest), 0.17% in OE2 (less dense) and 0.27% in OE3 (intermediate density). The classes of metabolites detected in thin-layer chromatography and confirmed through phytochemical surveys were steroids, saponins and phenolic compounds. The essential oil presented as major compounds safrole (74.24%), α-pinene, β-pinene and 1,8-cineole, demonstrating antimicrobial activity against all microorganisms studied. Further studies are needed to determine the minimum inhibitory concentration and confirm which isolated substance is responsible for this antimicrobial action.